Effect of different organic manures on production of Lepidium sativum under Morus based agroforestry system - Gautam, Krishan Lal; Bishist, Rohit; Thakur, Chaman Lal; Gautam, Kamini; Sharma , Harish; Sharma, Archana (Bangladesh Journal of Botany, 2022)
Agroforestry is a sustainable land use system that integrates trees and shrubs on farmlands and rural landscapes to enhance productivity, profitability, diversity and ecosystem sustainability. In the present study effect of different organic manures on production of Lepidium sativum (a veterinary galactogogue/medicinal herb) under open conditions and Morus alba based agroforestry system was investigated. The experiment comprised of 8 treatments. It was observed that treatment T7 recorded higher plant height whereas other growth and yield parameter were recorded to be maximum in treatment T6. Highest number of branches, number of main stem, number of pods, yield parameters were observed in treatment T6 while the lowest was recorded in treatment T4. From the economical point of view, the treatment T3 resulted in higher net return (1154.27 USD ha-1) and BC ratio (2.44). Bangladesh J. Bot. 51(4): 797-805, 2022 (December)